The Effect of Aromatherapy with Lavender Oil on the Health-Related Quality of Life in Patients with Fibromyalgia - Gulsah Yasa Ozturk; Ibrahim Bashan (Journal of Food Quality)
The aim of this study was to evaluate the effect of lavender oil, which has been used in complementary medicine as an aromatherapeutic, on the health-related quality of life in patients diagnosed with fibromyalgia and to determine the main volatile compounds of lavender oil with healing effects. Forty-two patients aged 18 years and over who were diagnosed with fibromyalgia according to the American College of Rheumatology 2010 diagnostic criteria and used lavender oil as an aromatherapeutic by applying it on the wrist or via inhalation for four weeks were included in this study. The Short-Form (SF)-36 Quality of Life Scale was administered to the patients at baseline and after four weeks of lavender oil treatment to determine whether there was any change in their quality of life. The averages and correlation levels between the scores were calculated with the paired-sample t-test taking p < 0.05 as the statistical significance limit. In addition, the chromatographic analysis of lavender oil was performed with the combined headspace solid-phase microextraction and gas chromatography-mass spectrometry methods. When the quality of life scores were evaluated at baseline and after four weeks of lavender oil treatment, improvements were detected in all the subscales of SF-36 at the end of the study. It was found that all the subscale scores, except for general health, were statistically significantly higher compared to the baseline scores (p < 0.05). The major volatile compounds detected in lavender oil were linalool (29.33%) and linalyl acetate (27.69%). The remaining main compounds were terpinolene, cis-ocimene, eucalyptol, and lavandulol in the order of frequency, which is consistent with the literature. To our knowledge, this is the first study investigating the effect of lavender oil aromatherapy on patients diagnosed with fibromyalgia, and our results support that lavender oil aromatherapy significantly improves the quality of life in these patients. However, further comprehensive studies are needed to confirm our findings.